(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To assess patient satisfaction with service quality at the Department of General Examination, 108 Military Central Hospital and finding out some related factors. Subjects and research methods: A cross-sectional descriptive study on 433 patients going to the hospital from April 2022 to July 2022. Tool for data collection was structure questionaire. Solfware SPSS 26.0 was used to data analysis. Research results: The average overall satisfaction score of patients is 3,54 ± 0,54, belonging to the level of satisfaction. Patients were highly satisfied with 4 contents: Medical examination results, staff’s skills and attitudes, medical examination and treatment costs, and landscape environment. Up to 89.9% of patients said they would return for medical examination. In 9 subjects about the characteristics of research subjects, the average satisfaction scores differed statistically significantly between groups with different levels of education, occupation and distance to the hospital.(p < 0.05). Conclusion: Patients have an overall satisfaction level of service quality at the Department of Examination is 3.54 ± 0.54, belonging to the level of satisfaction (5-level scale). The remaining four items on parking service, waiting time for medical examination, toilet, and waiting area reached acceptable levels.